Downregulated in renal carcinoma 1 (DRR1) mediates the differentiation of neural stem cells through transcriptional regulation. (21st June 2021) - Lu, Fangjin; Zhu, Lin; Jia, Xiaoyu; Wang, Jiao; Mu, Ping
Highlights: DRR1 is expressed in neural stem cells. DRR1 mediates the differentiation of neural stem cells. DRR1 participates in regulation the expression of several genes at the transcriptional level during the differentiation of neural stem cells. Abstract: Downregulated in renal carcinoma 1 (DRR1), also called family with sequence similarity 107, member A (FAM107A), is highly expressed in the nervous system. DRR1 has been found to be involved in neuronal survival, spine formation, and synaptic function. Recently, several studies have reported that DRR1 is expressed in neural stem cells (NSCs) and neural progenitor cells during the early stages of brain development. However, the mechanisms underlying the role and function of DRR1 in NSCs are poorly understood. To clarify the role of DRR1 in NSCs, we transfected DRR1 shRNA into primary NSCs and found that downregulation of DRR1 suppressed the differentiation of NSCs. To investigate the underlying mechanism in this case, chromatin immunoprecipitation sequencing (ChIP-seq) analysis was performed to identify the genes downstream of DRR1. Several genes, such as AHNAK, VAMP8, NOD1, and ACVR2B were identified to be downstream of DRR1 in NSCs.